Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/moo.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Vocal tract characteristics in Parkinsonʼs disease

Abstract: Parkinson's disease voice tremor is likely to be related to oscillatory movement in structures across the vocal tract rather than just the vocal folds. To progress clinical practice, more refined tools for the visual rating of tremor would be beneficial. How far voice tremor represents a functionally significant factor for speakers would also add to the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…We are the first study that investigated the use of VTL to identify voices of people with PD and found that VTL parameters outperformed the features reported in the literature that are related to perturbation of glottal vibration, such as jitter, shimmer, pitch frequency, and harmonics ratio. The finding in this study suggests and supports the argument in 35 that the neuro-physiology change in PD patients is manifested more in the change of vocal tract control compared to glottal vibration or air pressure control by the lung. This opens the potential for computerized and remote monitoring of people with PD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We are the first study that investigated the use of VTL to identify voices of people with PD and found that VTL parameters outperformed the features reported in the literature that are related to perturbation of glottal vibration, such as jitter, shimmer, pitch frequency, and harmonics ratio. The finding in this study suggests and supports the argument in 35 that the neuro-physiology change in PD patients is manifested more in the change of vocal tract control compared to glottal vibration or air pressure control by the lung. This opens the potential for computerized and remote monitoring of people with PD.…”
Section: Discussionsupporting
confidence: 89%
“…It is commonly assumed that Parkinsonian dysarthria is affected by the abnormal vibration of the vocal cords, such as the inadequate or excessive closing of the vocal cords and irregular or asymmetrical vocal fold, as well as a tremor in its muscles 8 , 34 , 35 . A total of 6 parameters related to the periodicity and stability of glottal vibration were extracted from each recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the abnormal vibration of the vocal cords also affects dysarthria. Laryngopharyngeal involvement manifests as vocal fatigue, vocal breaks, tremor and the inability to make sound 12 , 13 . These manifestations may lead to the inadequate or excessive closing of the vocal cords and irregular or asymmetrical vocal fold motion during phonation 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…2,18,22 Similarly, patients with lung cancer, coexisting throat symptoms, dysphagia, and neurologic diseases such as Parkinson disease or essential tremor also warrant heightened vigilance from providers. 23,24 Although concern regarding potential overdiagnosis of reflux-related voice disorders has been raised, gastroesophageal reflux was related to ≥30 days of voice-related health care utilization (Table 5). 2527 Whether this association is due to a pathologic link, coprevalence, or presumptive reflux diagnosis cannot be determined.…”
Section: Discussionmentioning
confidence: 99%